'My Tongue Gets t-t-t-': Words, Sense, and Vocal Presence in Van Morrison's It's Too Late to Stop Now. Issue 1 (14th March 2016) - ELLIOTT, RICHARD
Abstract: Van Morrison's live version of his song 'Cyprus Avenue' on the 1974 album It's Too Late to Stop Now provides an example of the authority of the singer's voice and of how it leads and demands submission from musicians, songs, and audience. Morrison's voice constantly suggests that it is reflecting important experience and can be understood both as an attempt to capture something and as a post-hoc witnessing or testimony. Through the example of Morrison's work, and of It's Too Late to Stop Now in particular, this article explores the location of the voice in terms of the body and of particular places and histories. It then proceeds to a reflection on the relationship between the performing voice as producer of sound, noise, and music and the poetic voice that provides the words and visions upon which the performing voice goes to work. It concludes by focusing on a moment within 'Cyprus Avenue' where Morrison performs the act of being tongue-tied, discussing this as an example of 'aesthetic stutter'. Throughout, attention is also paid to how other voices (particularly those of rock critics) connect to Morrison's voice by attempting to describe it, re-perform it, or explain it.